Moving Knowledge into Action Through Communities of Practice: Multiple Case Studies of Successful System Change to Improve the Health of Older Adults - James Conklin; Anita Kothari; Paul Stolee; Larry Chambers; Ken LeClair (SAGE Open)
This monograph reports the results of a three-year multiple case study of nine knowledge-to-action (KTA) initiatives mobilized in communities of practice (C0Ps) operating in Ontario's seniors' health system. A multiple case study design was used to conduct nine case studies through a combination of case study and ethnographic methods. Deductive analytical methods were used to answer two broad research questions about the KTA processes mobilized through the CoPs, and about the roles played by CoP members and other stakeholders. Inductive analytical methods were used to reveal the patterns of interaction characteristic of the CoPs. These CoPs acted as flexible and temporary social forms with specific characteristics and processes allowing them to integrate explicit and tacit knowledge to resolve the unique contextual challenges of health practices. Our findings suggest that these CoPs often developed a double-loop learning process that is well suited to responding to adaptive challenges and wicked problems. Conclusions from this qualitative study are not generalizable to all situations and contexts. Findings suggest that the concept of "knowledge-to-action" be supplemented by a concept of "action-to-knowledge" that recognizes that important initiatives are often incubated in the action of health care delivery when dedicated professionals come together to tackle intractable issues. This is the first multiple case study of CoPs in the Canadian health system. The study shows that CoPs can act as the junction for the rational epistemology of science and the narrative epistemology of practice.